Deep freeze [compact disc, unabridged] - Sandford, John, 1944 February 23- (Sandford, John, 1944 February 23- Virgil Flowers novels., 2017)
Twenty-year class reunions are a time for memories, good, bad, and--as Virgil Flowers is about to find out--deadly. A woman's death may be connected to a high school class of twenty years ago.